Turunkan Stunting Melalui Program Dapur Sehat Atasi Stunting (DASHAT) Di Desa Banjaragung Kabupaten Jepara - Anam, Khoiril; Anies Setiowati; Shofia, Eva Ulfiatus; Jelita, Moren Nanda; Palgunadi Palgunadi; Rinta Amalia (Universitas Negeri Semarang, 2025)
The research aimed to assess the impact of the Healthy Kitchen to Address Stunting (DASHAT) program in reducing stunting rates in Banjaragung Village. With a high stunting rate of 18%, this issue is a major focus for the UNNES GIAT 9 program. Stunting is primarily caused by inadequate nutrition in toddlers. The implementation involved collecting data on DASHAT program recipients, executing the program, and monitoring its impact twice a week. After monitoring, positive developments were noted in 15 children, with improvements in final measurement results. The research concludes that the DASHAT program has a positive effect and is an effective strategy to reduce stunting in Banjaragung Village.